‘People [...] Should Stand Like Men and Demand Their Rights and Liberties’ : le motif de la dignité dans le droit de résistance chez Milton - Christopher Hamel (Etudes Epistémè)
There is no real conceptual opposition between Milton’s contractualism and Milton’s republicanism. One can notably see in the idea of ‘dignity’, which is developed in The Tenure of Kings and Magistrates and in other political writings to justify the right of resistance to arbitrary power, a reconciliation between modern jusnaturalism and classical republican thought.